From Data to Design: An Investigation of Curriculum Development Needs - Aghnia Assifa Nadia; Ayu Muliahayati Nashir; Zaitun Qamariah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study highlights the importance of needs analysis in developing learner-centered curricula. Using a library research approach, it explores how investigative techniques—such as interviews, surveys, and classroom observations—can effectively uncover both explicit and implicit student needs. The analysis reveals that triangulating these techniques provides a more holistic and valid understanding of learners. Teachers are encouraged to take on the role of